Front Cover: Ultrafine SnO2 Nanocrystals Self‐Anchored in Carbon for Stable Lithium Storage (ChemElectroChem 17/2018). Issue 17 (25th July 2018) - Fu, Shuting; Wu, Qili; He, Shiman; Tong, Shengfu; Yang, Xianfeng; Meng, Yuying; Wu, Mingmei
Abstract : The Front Cover shows ultrafine SnO2 nanocrystals embedded in carbon. The produced material with such structure exhibits a superior electrochemical performance, which can potentially be used in electric vehicles. More information can be found in the Article by S. Fu et al. onpage 2341 in Issue 17, 2018 (DOI:10.1002/celc.201800631 ).